Relationship between Knowledge and Family Preparedness in Facing Dengue Fever in Lhokseumawe City - Ida Yustina; Fazidah Aguslina Siregar; Zulfahmi (Britain International for Academic Research (BIAR) Publisher, 2020)
This study aims to describe relationship between knowledge and family preparedness in facing dengue fever in Lhokseumawe City. The study is conducted in 20 villages, in 3 districts namely Muara Dua District, Banda Sakti, Muara Satu Lhokseumawe City. The selection of this location is considered to be a DHF endemic village where every year DHF free larvae cases are found below 95 percent with the number of cases 111 in 2018. The result shows that Family preparedness in the face of dengue fever in Lhokseumawe City is mostly 76 families ready (66.1%). Knowledge has no effect on family preparedness in the face of dengue fever in Lhokseumawe City (p = 0.073).